2018
DOI: 10.3892/br.2018.1110
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene expression as one of the key mechanisms involved in radiation‑induced bystander effect (Review)

Abstract: The radiation-induced bystander effect (RIBE) refers to the manifestation of responses by non-targeted/non-hit cells or tissues situated in proximity to cells and tissues directly exposed to ionizing radiation (IR). The RIBE is elicited by agents and factors released by IR-hit cells. The growing body of data suggests that the underlying mechanisms of the RIBE are multifaceted depending both on the biological (characteristics of directly IR-exposed cells, bystander cells, intercellular milieu) and the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 81 publications
0
20
0
1
Order By: Relevance
“…It should be noted that ROS can serve both as inter- or intracellular messengers [ 60 , 61 , 62 ]. Reactive oxygen or nitrogen [ 63 ] species released by cells can serve as signal particles which elicit the radiation-induced bystander effect [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that ROS can serve both as inter- or intracellular messengers [ 60 , 61 , 62 ]. Reactive oxygen or nitrogen [ 63 ] species released by cells can serve as signal particles which elicit the radiation-induced bystander effect [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the impairment of DTC patients' parathyroid function after RAI is still unclear. It has been reported that a non-targeted effect of ionizing radiation may cause diminished parathyroid function after RAI, called a "bystander effect" on adjacent cells (6,11). Guven et al reported that PTH decreased in the short term but generally did not lead to hypocalcemia (6).…”
Section: Discussionmentioning
confidence: 99%
“…So far, global gene expression has been assessed in cells treated with conditioned media from irradiated cells or in co-culture (for review see ref. 59 ) using microarray chips, but the coverage is too low, and the results do not reflect the magnitude of the effects, rendering this technology effectively obsolete. Furthermore, the effects of irradiated cells on non-irradiated cells and vice versa also require investigation.…”
Section: The Bystander Effectmentioning
confidence: 99%